Takyif (Adaptasi) Fiqih dan Mansya'ul Khilaf (Akar Perbedaan) Multi Level Marketing (MLM) - Supriadi, Slamet; , Dr. Muinudinillaah Basri, MA (2015)
MLM is a contemporary transaction type that requires an explanation of its law. MLM has a complex marketing system that influence the differences of fatwas among scholars. Accordingly, the study of Takyef (adaptation) Feqh and Manshaul Khelaf (Source of Differences) are needed. By knowing the type of its contract, we can provide on its own proper laws. And by knowing the background difference of scholars opinion, the accuracy level to understand the problem will be higher. The research was done by using a phenomenological qualitative approach particularly the inductive analysis conducted by collecting a variety of literature that speaks about MLM, then comparing all Takyef Feqh following by analysys of the differences. Almost all types of existing Takyef Feqh been collected for review, both from inside and outside the country. Performed a detailed discussion on all components or stages in MLM marketing system and the type of contract therein. The results of the study showed that conventional MLM still contains many things that are forbidden by the Shari'a, while MLM labeled Shariah in Indonesia still does not meet the requirements set by the middle east scholars.